Introduction of telemedicine and new technologies in the Colombian health system - Caro Rodríguez, Derly Viviana (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
The research examined the implementation of telemedicine and new technologies in healthcare in Colombia. A mixed-method approach was employed, combining qualitative and quantitative methods to explore the topic. Relevant documents and studies were analyzed, identifying challenges and opportunities in telemedicine. Findings highlighted the importance of healthcare personnel training, integration of administrative and financial aspects, and ongoing evaluation of outcomes to ensure the success of telemedicine. Barriers such as the digital divide and ethical issues were identified. The research concluded that telemedicine offers an innovative solution to enhance access, efficiency, and quality of healthcare in Colombia but requires addressing significant challenges for equitable and effective implementation